Analisis Klaster dan Prediksi Dinamika Produksi Padi Sawah menggunakan K-Means dan Adams-Bashforth-Moulton di Kabupaten Banyumas - Wisnu; Ambar Winarni; Istifada Nurul Hayati (Universitas Cokroaminoto Palopo, 2026)
This study aims to classify rice-farming areas in Banyumas Regency based on differences in rice production characteristics between regions that have the potential to influence rice production planning and distribution. This study was conducted to support food security in line with Indonesia's national development vision for 2045. The data used included rice production volume and rice field area. Cluster analysis was performed using the K-Means method with the determination of the optimal number of clusters through the Elbow method, resulting in three regional clusters, namely low, medium, and high rice production clusters, which reflect the differences in rice production characteristics between subdistricts in Banyumas Regency. Rice production dynamics were modeled using the Verhulst growth model, which was solved numerically using the fourth-order Runge Kutta method, followed by the Adams-Bashforth-Moulton method to predict rice production. Predictions were made for 2025, 2030, and 2045 to illustrate rice production trends over several time periods. The main analysis of this study focused on the period up to 2030 because the model did not include several important external factors that could potentially affect rice production in the long term. The error analysis results showed that the error values in the predictions for the 2025 and 2030 periods were relatively small, indicating that the model was able to represent rice production dynamics well during those periods. Predictions up to 2045 are presented as a mathematical illustration of long-term trends and are not used as the main basis for error evaluation or drawing conclusions. The results of this study are expected to be used as preliminary considerations for local governments in formulating rice production plans, taking into account the different characteristics of regional clusters and the predicted rice production in Banyumas Regency.